Pengaruh Nilai Tukar, Tingkat Pertumbuhan Ekonomi, Dan Tingkat Inflasi Terhadap Jakarta Islamic Index - Surepno, Surepno; Agustina, Aqinatul Munawaroh; Naim, Abdul Haris (AKTSAR: Jurnal Akuntansi Syariah, 2019)
The purpose of this study was to analyze the effect of the rupiah exchange rate, economic growth and inflation on the Jakarta Islamic Index. This type of research is quantitative research with secondary data sources. The sampling method uses purposive sampling method. The data analysis method used in this research is multiple linear regression analysis. The results of this study indicate that partially the rupiah exchange rate has a significant effect on the Jakarta Islamic Index while economic growth and inflation have no significant effect on the Jakarta Islamic Index. Simultaneously variables of the rupiah exchange rate, economic growth, and inflation significantly influence the Jakarta Islamic Index.